Development Digital Course Book Management Learning in ITKeS Muhammadiyah Sidrap - Roni Roni; Kassaming Kassaming; Sam Hermansyah (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2023)
Use digital books are urgently needed in online learning in the era of the Covid-19 pandemic. For increase quality learning , development curriculum , innovation learning , and quality nor completeness facilities and infrastructure. Research This done with use R&D (Research and Development) approach . Study This aim For 1) describe level need student to digital management book learning , 2) describe level validity digital management book learning , 3) describe level practicality digital management book learning . Study This developed with using a 4D model (define, design, development, disseminate). Study This carried out in the study in ITKeS Muhammadiyah Sidrap .